Audio Description as a Pedagogical Tool in the Foreign Language Classroom: An Analysis of Student Perceptions of Difficulty, Usefulness and Learning Progress - Bausells-Espín, Adriana (Journal of Audiovisual Translation, 2022)
Audio description (AD) is an intersemiotic mode of audiovisual translation where images are translated into words to facilitate access to visual content for visually-impaired audiences. Over the last decade, it has gained prominence in foreign language research, as its formal particularities and condition as a communication-oriented and process-based activity present a fertile ground for designing innovative classroom tasks. This research was conducted with students of Spanish at the University of Manchester, and it investigates participants’ perceptions about a classroom AD project. The exploratory analysis of quantitative and qualitative data from participants’ responses to end-of-project questionnaires leads to the formulation of a ‘triple-connection hypothesis’: a direct relationship between perceptions of difficulty of the main challenges of AD, perceptions of usefulness of AD for developing the skills required to overcome those challenges, and perceptions of own learning progress thanks to AD. The findings show that AD is perceived by students as especially useful for developing integrated skills, communicative skills and lexical skills, to a greater or lesser extent depending on the difficulty perceived. Lay Summary Audio description (AD) is an additional voice that describes what happens in a TV show, a movie or a theatre play when characters are not speaking. This helps people with visual problems to follow the plot. AD describes characters’ expressions or movements, places or objects, or reads text that appears on screen. It is a special type of translation: instead of translating from words to words, it translates from images to words. Recently, AD has become more available and popular, catching the attention of foreign language teachers. They have started using it in class, creating activities where students write audio descriptions to improve language skills, such as vocabulary, or record them to practice speaking. Creating an AD requires students to use clear and direct language, use summarising skills, and make a lot of careful choices. It also helps them learn about the needs of people with visual difficulties. So far, teachers have reported positive results. To continue exploring how useful AD activities are for language learning, we did an AD classroom project with students of Spanish, and we collected their opinions about it. This information can help teachers design truly beneficial AD activities. Our students completed a survey at the end of the project to tell us how difficult AD had been for them, how useful they found it for language learning, and how much it helped them improve. We discovered that when students found AD difficult, they also found it more useful, and they learned more. We also discovered the opposite: when they found it less difficult, they also found it less useful, and they learned less. Finally, we discovered that AD especially helped them to improve communication and speaking abilities, to build vocabulary and sound natural, and to practice several skills at once.